2016
DOI: 10.1073/pnas.1524498113
|View full text |Cite|
|
Sign up to set email alerts
|

Enterovirus D68 receptor requirements unveiled by haploid genetics

Abstract: Enterovirus D68 (EV-D68) is an emerging pathogen that can cause severe respiratory disease and is associated with cases of paralysis, especially among children. Heretofore, information on host factor requirements for EV-D68 infection is scarce. Haploid genetic screening is a powerful tool to reveal factors involved in the entry of pathogens. We performed a genome-wide haploid screen with the EV-D68 prototype Fermon strain to obtain a comprehensive overview of cellular factors supporting EV-D68 infection. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(128 citation statements)
references
References 32 publications
7
120
0
1
Order By: Relevance
“…Our data clearly shows that cotton rats are permissive to EV-D68 and that it replicates in respiratory airways, although with differing infection profiles among three strains, ATCC being the weakest, while VANBT showed the strongest infection and replication profile (Fig 1B). These differences in viral replication could represent different evolutionary stages of the three strains that can affect at various levels of replication of these viruses or they may differentially use an alternative, nonsialylated receptor to infect the cells [52]. Although the replication cycle of VANBT appeared to be short-lived, its profile of viral titer in the nose over time (showing clear virus eclipse at 4 h, rising quickly and reaching a peak by 10 h p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Our data clearly shows that cotton rats are permissive to EV-D68 and that it replicates in respiratory airways, although with differing infection profiles among three strains, ATCC being the weakest, while VANBT showed the strongest infection and replication profile (Fig 1B). These differences in viral replication could represent different evolutionary stages of the three strains that can affect at various levels of replication of these viruses or they may differentially use an alternative, nonsialylated receptor to infect the cells [52]. Although the replication cycle of VANBT appeared to be short-lived, its profile of viral titer in the nose over time (showing clear virus eclipse at 4 h, rising quickly and reaching a peak by 10 h p.i.…”
Section: Discussionmentioning
confidence: 99%
“…The atomic structure of rhinovirus-C also revealed a potential binding site for sialic acids in a sequence-conserved surface depression [11 ]. Sialic acids were recently shown to also facilitate entry of EV-D68 [12,13]. Targeting sialic acid (reviewed in Ref.…”
Section: Direct-acting Antivirals Entry Inhibitorsmentioning
confidence: 99%
“…Investigation of the role of Sia in infections by six EV-D68 strains isolated from patients during the period from 2009 to 2010 in comparison with the prototype Fermon strain isolated more than 50 years ago showed that Sia-deficient cells and sialidase-treated cells were resistant to infections by strains 670 (clade A), 2042 510 Nongluk Sriwilaijaroen and Yasuo Suzuki (clade B), and 2284 (clade C) as in the case of the Fermon strain [89] but were sensitive to infections by the other three strains, 947 (clade B), 1348 (clade A), and 742 (clade A), and can thus be classified as Sia-dependent and Sia-independent strains, respectively [95]. The use of knockout cell lines and gene reconstitution, glycan array screening, infection inhibition assays by receptor analogues, and co-crystal structure analysis have indicated that both α2-3Neu5Ac and α2-6Neu5Ac on either lactose or lactosamine can be receptors for virus infection [89,95], possibly explaining why EV-D68 infection causes a wide spectrum of illnesses.…”
Section: Picornaviridaementioning
confidence: 99%
“…(2) Viral lectins are potential targets because they are required for the crucial first stage of the virus life cycle, and several antiviral lectins have been developed, but most of them act against common pathogens causing widespread severe and life-threatening diseases in humans such as sialylmimetics against rotavirus infection [183], trivalent sialic acid-based inhibitors to treat EV-D68 infections [184], and 6 0 SLN-lipo PGA (Neu5Acα2-6Galβ1-4GlcNAcβ1-eicosanoyl chain poly-α-L-glutamic acid) against influenza epidemics and pandemics [185]. Some viruses are Sia-independent viruses, such as rotavirus human strains K8, KU, MO, and Wa [121] and EV-D68 strains 947, 1348, and 742 [95]. Some Sia-binding pathogens, such as MERS-CoV, CVA24v, JCPyV, and MCPyV, use more than one receptor for infection.…”
mentioning
confidence: 99%